Challenges of Sharia Compliance Audits in Islamic Banking: An Analysis of Fintech Developments in Indonesia - Yulia Andriani; Ahmad Habibi; Muhammad Iqbal Fasa (International Publisher, 2025)
Digital transformation has encouraged Islamic banking in Indonesia to integrate financial technology (Fintech) to improve efficiency and competitiveness. This study aims to examine the application of fintech in Islamic banking, its impact on sharia compliance, and evaluate the effectiveness of supervision in the digital age. This study uses a library approach with qualitative content analysis, as well as the theoretical framework of diffusion of innovation and Islamic financial law. The study found that although Fintech facilitates the implementation of Sharia principles through profit-sharing/buying and selling schemes and contract transparency, there are tensions between digital automation and Sharia accountability that could potentially lead to violations of Islamic principles if oversight is not strict. Therefore, the study concludes that there is an urgent need to develop a digital Sharia audit framework that is capable of performing a Sharia-compliant test directly on the system's source code, as well as encouraging collaborative innovation to embed compliance tools into the core of the technology.